2022
DOI: 10.3389/fpubh.2022.835092
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology, Drug Susceptibility, and Clinical Risk Factors in Patients With Invasive Aspergillosis

Abstract: BackgroundThis study aimed to investigate the Aspergillus species distribution, antifungal sensitivities, clinical characteristics, and risk factors of patients with invasive aspergillosis (IA) in a tertiary teaching hospital in Anhui Province.MethodsIn the present study, 156 Aspergillus isolates were collected from patients admitted to a 2,800-bed comprehensive hospital between January 2019 and April 2021. The epidemiology of Aspergillus species was well-examined, and its antifungal susceptibility was specifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 54 publications
2
8
0
Order By: Relevance
“…Specifically, this comprised of 3.3% (2/60) resistance solely to amphotericin B, 1.7% to voriconazole, and 1.7% exhibited resistance to both itraconazole and amphotericin B. This azole-resistance rate is consistent with previous studies in Asia, including China, [35][36][37] Japan, 38 Pakistan, 39 Korea, 40 where the azole-resistance was less than 10%. However, azole resistance rates were significantly higher in other regions.…”
Section: Discussionsupporting
confidence: 88%
“…Specifically, this comprised of 3.3% (2/60) resistance solely to amphotericin B, 1.7% to voriconazole, and 1.7% exhibited resistance to both itraconazole and amphotericin B. This azole-resistance rate is consistent with previous studies in Asia, including China, [35][36][37] Japan, 38 Pakistan, 39 Korea, 40 where the azole-resistance was less than 10%. However, azole resistance rates were significantly higher in other regions.…”
Section: Discussionsupporting
confidence: 88%
“…Due to the fact that previous literature on the identification of IPA has established evaluation criteria specific to different populations, such as individuals with blood disorders or ICU patients, who are considered high-risk groups, there is currently no universal standard applicable to all populations.A retrospective study in hospitalized patients with positive Aspergillus culture from lower airway samples found that 66.6% of those fulfilled putative invasive pulmonary aspergillosis [7] .Our research referenced its evaluation criteria and found that the proportion of IPA was 52.8%. In this study, the most common underlying systemic condition was tracheal and bronchial diseases, mainly including pulmonary/bronchial inflammation and COPD, as previous reports [15] . Thus, tracheal and bronchial diseases were identified as an important risk factor for IPA.…”
Section: Discussionsupporting
confidence: 76%
“…The prevalence of azole-resistant Aspergillus species varies geographically. Our study found that 2 out of 276 samples (0.72%) were resistant to VRC and non-wild type for ITC, which is lower compared to Beijing (4.3%), 60 Shanghai (3.57–7.02%), 61 , 62 and Anhui (5.79%) 63 in China. In a separate study conducted in China, A. fumigatus isolates were collected from various regions, revealing a 4.4% frequency of azole resistance.…”
Section: Discussionmentioning
confidence: 52%